A radical cascade reaction of aza-1, 6-enyne compounds using allyltributyltin. Issue 48 (1st December 2016) - Kamimura, Akio; Miyazaki, Koichiro; Kawamoto, Takuji; Uno, Hidemitsu
Abstract: The radical cascade reaction of allyltin with aza-1, 6-enyne compounds was studied. Optically active aza-1, 6-enynes underwent a radical cascade process in the presence of a high concentration of allyltributyltin to give stannolanes as the major isomer. Piperidines were also observed in small amounts when an allylic unit was introduced stereoselectively to the trans -position of the aryl group at the C2 position. The yield of the products dramatically decreased with concentrations of tin reagent. The E/Z selectivity at the exomethylene group in piperidine depended on the reaction temperature, and it almost doubled when the reaction was carried out at 30 °C. In this study, the reaction mechanism of the radical cascade is discussed. Graphical abstract: